Literature Review Hambatan Perilaku Kepatuhan Dalam Konsumsi Tablet Besi Pada Ibu Hamil - Diana Putri (STIKES Columbia Asia Medan, 2025)
Anemia during pregnancy remains a significant public health challenge, with iron supplementation recommended as the primary preventive strategy. However, compliance with iron tablet consumption among pregnant women continues to be low in many settings. This study aims to review existing literature to identify barriers that hinder adherence to iron supplementation. A systematic literature review was conducted by screening publications from 2015 to 2025, retrieved from major databases such as PubMed, Scopus, and ScienceDirect. Thematic synthesis was applied to analyze findings across selected studies. Results revealed three major categories of barriers: internal factors such as limited knowledge, perceived low risk of anemia, and side effects; social factors including lack of family support, cultural norms, and insufficient counseling from health providers; and systemic factors such as limited supplement availability and inadequate quality of antenatal services. These findings highlight that compliance is not merely an individual issue but also shaped by social and structural contexts. Implications suggest the need for multidimensional interventions, involving health education, family engagement, and strengthened health system support to improve maternal adherence to iron supplementation.